Community sanctions: Offenders' perceptions about their appropriateness. (August 2021) - Andrade, Joana; Cruz, Ana Rita; Cunha, Olga; Gonçalves, Rui Abrunhosa; Rodrigues, Andreia Castro
This study analyzed offenders' perceptions about distinct sanctions and their adequacy for different crimes, checking if these ideas apply to their crime. We covered a total of 163 adult offenders who were sanctioned with a non-custodial order. The results show that participants tended to express a punitive attitude toward crime, apart from their offenses. Participants who committed driving or drug trafficking offenses were those that revealed congruence regarding the adequacy of the sentence and the usefulness of the sanction imposed. Regarding sentences' purposes, we noticed most participants considered punishment and general deterrence as the primary purposes. The main contribution of this study lies in its educational value about the cognitive particularities and specific needs of each type of offender. Not attending to offenders' perceptions regarding sanctions may function as an obstacle for an efficient implementation of the Justice, in terms of their adherence to the sanctions, and consequently their rehabilitation.